Strategi Pengembangan Ekonomi Kreatif Dengan Metode Triple Helix (Studi Pada UMKM Kreatif di Kota Medan) - Zul Asfi Arroyhan Daulay (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2018)
The purpose of this reaserch is to analyze the development of Creative economy in the City of Medan and the pattern of strategies for developing creative economy with a SWOT analysis approach through the Triple Helix method. Methodology / Design The research used in this study is a qualitative method by conducting surveys and interviews on the parties concerned. By using SWOT analysis and development strategy with triple helix concept to obtain expected research result. The result of the research indicate that the development of the creative economy for the craft sub-sector is in the third position after culinary and fashion. The pattern of interaction between the three actors (actors, government and academics) must collaborate and symbiosis in mutualism in designing and developing the creative economy and the strategy used to develop the creative economy is by aggressive strategy or S-0 strategy which uses the power to take advantage of opportunities.